Locative Imperatives in Javanese - Suhandano Suhandano (Journal of Language and Literature, 2023)
Javanese is a member of the Western Austronesian language, a sub-family of the Austronesian language family. Languages in this sub-family are known in linguistic literature as having an exceptional feature in their voice system among the world’s languages and continue to be exciting issues in the theory of syntax. This paper investigates the voice system in Javanese and focuses on the locative imperative clauses’ voice system. Data are collected from the Javanese spoken in Yogyakarta at the ngoko level. This study demonstrates that Javanese has five variants of locative imperative clauses: intransitive locative imperatives, active locative imperatives, passive locative imperatives, locative imperatives with actor focus, and locative imperatives with locative focus. The five variants of imperatives reflect the voice system of the clauses. There are two voice systems of locative imperatives in Javanese: a two-voice system and a multiple-voice system. Intransitive locative imperatives, active locative imperatives, and passive locative imperatives are imperatives within the two-voice or active-passive voice systems. The other two variants of locative imperatives, the locative imperatives with actor focus and the locative imperatives with locative focus, are types of locatives imperatives within the multiple voice system. The existence of the two voice systems in Javanese indicates that this language is in the process of changing from a multiple-voice language to a two-voice language.